Encapsulation of food flavors using a natural crosslinking agent - Buldur, Perihan Merve; Kok, Fatma Nese (Elsevier BV, 2012)
INTRODUCTION Flavors lose their effect beginning from the production step due to their volatile and oxidation labile nature. To prevent this problem, encapsulation of flavors into different materials (e.g. gelatin, gum arabic, whey proteins, pectin, etc) is a well known method. Flavour encapsulation is accomplished by a variety of methods, such as spray drying, extrusion, freeze drying, coacervation and adsorption techniques1. In this study, complex coacervation method was used to encapsulate food flavors into gum arabic/gelatin mixture. Complex coacervation involves more than one colloid and caused by the interaction of two oppositely charged colloids between a poly-anion and a poly-cation, both water-soluble.